ANALISIS RETORIKA DAN PROPAGANDA ANIES BASWEDAN: EDISI KE-3 TAHUN 2024 - Ratih Saspira; Yusnita , Titien; Muslikhah , Febri Palupi (Fakultas Ilmu Dakwah dan Komunikasi, 2025)
Ahead of the general election, the third edition of the debate between presidential candidate Anies Baswedan. This debate is related to the work program that will be carried out after being elected as president of the Republic of Indonesia. The third edition of the debate with the theme